Fibre waviness in pultruded bridge deck profiles: Geometric characterisation and consequences on ultimate behaviour. (1st August 2018) - Sebastian, W.M.
Abstract: Conventional tests cannot be used to establish the important influence of fibre waviness, a manufacturing legacy at the flange-web joints (FWJs) of pultruded GFRP bridge decks, on the local ultimate behaviour of such decks. Hence a novel, simple and reliable three-step experimental scheme for that purpose is presented herein, using one pultruded deck profile as an exemplar. First, the joints to be targeted for testing - namely those within the single deck unit and the hybrid joints formed by bonding deck units together - are identified. Second, an effective manual method is put forward to map this waviness at the FWJs. Third, a test is introduced which enables statically determinate loading (via an adjoining flange) of one joint at a time, while also ensuring continuity between this joint and the remaining deck so that the real load paths within the deck are preserved. During the tests failure always occurred by fracture of the wavy fibre-resin interfaces within the FWJs. In the hybrid joints, this failure occurred on the same side of the adhesive layer as the load. The strongest joint had the least waviness. For the flange-single web (but not the flange-double web) joint, bonding transformed the wavy fracture pattern and quadrupled the failure load. It is concluded that this simple test, which also reveals the influence of fibre waviness on the flange's local flexural stiffness, can be further used to characterise joint fatigue performance.